Muslim Women in Mainland China and Macau Old Barriers, New Solutions - 雷祖善博士, Joseph Abraham Levi (E- Revista de Estudos Interculturais, 2021)
Using as a springboard the wide spectrum of Chinese racial groups and ethno-linguistic, “foreign”(sub)groups residing in the Celestial Empire, this study concentrates on the last one hundred and six years of Chinese history (1912-2018), thus analyzing howsome Chinese cities and/or regions, including the Macau Special Administrative Region of the People’s Republic of China,have managed to reconcile past with present, thus transforming once-troubled or troublesome issues, as in the case of Muslim presence within China, into a positive and reinvigorating force.Besides the obvious economic drive, there appears to have been a sincere desire to include and integrate this “foreign”element into the daily life of the new Republic of China 中華民國Zhōnghuá Mínguó, (1912-1949). Thus, particular attention will be given to the role played by Chinese women within these post-1912, “foreign”communities and, as for 澳門Macau, the post-1999 handover to China by the Portuguese on December 20, 1999.Though oftentimes considered as mere “consumers”and not “makers;”hence, allegedly not contributing to the overall “welfare”of the Country, Chinese women of “foreign”ethnicity who also happened to be Muslim, were eventually able to show the New Republicthat the 女工, nǚgōng—work done by women, in and outside the household—should instead be considered “productive”and, better yet, it should be seen as a positive sign within the new vision of Chinese nationalism where social class, race, ethnicity, language/dialect, religion, and gender all contributed to the welfare of the Country, or rather, the then-young Republic of China 中華民國,Zhōnghuá Mínguó. Finally, I will look at Muslim women of Uighur維吾爾, wéi wúĕr, and Huí回background who also contributed to this new vision